Does Easily Accessible Nutritional Labelling Increase Consumption of Healthy Meals away from Home? A Field Experiment Measuring the Impact of a Point-of-Purchase Healthy Symbol on Lunch Sales - Linda Thunström; Jonas Nordström (Lund University, School of Economics and Management, Department of Economics, 2011)
This paper analyses the effect on meal consumption away from home of a point-of-purchase healthy symbol. We base the analysis on a field experiment in a lunch restaurant. Our results suggest that meal consumption does not increase if the meal is labeled with a healthy symbol. Also, the mean nutritional content of meals consumed seems unaffected by the introduction of a healthy labeled meal on the menu. Even if easily accessible and understood, menu labeling therefore seems inefficient in promoting healthier meal choices. Factors influencing meal consumption are meal ingredients and the order of the meal on the menu.
Keywords: D12; I10; 330; Consumer economics; food labelling; experiment; health